A highly selective fluorescent probe for direct detection and isolation of mouse embryonic stem cells. Issue 21 (1st November 2015) - Chandran, Yogeswari; Kang, Nam-Young; Park, Sung-Jin; Husen Alamudi, Samira; Kim, Jun-Young; Sahu, Srikanta; Su, Dongdong; Lee, Jungyeol; Vendrell, Marc; Chang, Young-Tae
Graphical abstract: Abstract: Stem cell research has gathered immense attention in the past decade due to the remarkable ability of stem cells for self-renewal and tissue-specific differentiation. Despite having numerous advancements in stem cell isolation and manipulation techniques, there is a need for highly reliable probes for the specific detection of live stem cells. Herein we developed a new fluorescence probe (CDy9 ) with high selectivity for mouse embryonic stem cells.CDy9 allows the detection and isolation of intact stem cells with marginal impact on their function and capabilities.